Evaluating the effectiveness of a conflict resolution and resilience building bespoke educational workshop for South Australia midwifery students: A pre-post measure education study - Simpson, N.; Vernon, R.A.; Briley, A.L.; Esterman, A.J.; Steen, Mary (2025)
Background: Workplace bullying, and violence are well-recognised concerns within the midwifery profession. Research suggests midwifery students are exposed to bullying in clinical and education settings, impacting their professional and personal lives. A potential solution to this negative phenomenon experienced is the inclusion of conflict resolution and resilience building education within the Bachelor of Midwifery degree, which may equip midwifery students with the skills to manage and address conflict in the workplace. Aim: To evaluate the effectiveness of a conflict resolution and resilience building education workshop for second-year midwifery students in South Australia. Method: This paper focuses on data from phase 1 of a larger explanatory sequential mixed methods study. A semi-structured questionnaire and validated conflict measurement tool were used to examine students’ experiences of workplace bullying, and violence. A previously published research protocol guided this study. The study was not registered as a clinical trial as it used a pre-post measure of an education program that was included in the curriculum, for a singular group of students. Results: Thirty-three midwifery students in South Australia participated in both the pre- and 1-week post-education data collection. Only 10 of the 33 students who completed the pre- and 1-week post-education data, completed the 3-month post-education data collection. Midwifery students’ knowledge and level of confidence improved following conflict resolution and resilience building education. Conclusion: The inclusion of conflict resolution and resilience building in midwifery curriculum, strengthened students’ knowledge and understanding of conflict in the workplace. Students’ confidence levels in managing subtle forms of workplace bullying, and violence improved, however their confidence addressing confrontational styles of conflict showed little change, highlighting that conflict resolution and resilience education should be scaffolded throughout their curriculum to better equip students to manage conflict in the workplace.